A de novo microtriplication at 4q21.21‐q21.22 in a patient with a vascular malignant hemangioma, elongated sigmoid colon, developmental delay, and absence of speech. Issue 8 (10th June 2016) - Lebedev, Igor N.; Nazarenko, Lyudmila P.; Skryabin, Nikolay A.; Babushkina, Nadezhda P.; Kashevarova, Anna A.
Abstract : The widespread application of array comparative genomic hybridization (aCGH) has provided new insights into the clinical significance of copy number variations (CNVs) in the human genome. Many microdeletion syndromes have recently been linked to corresponding reciprocal microduplication syndromes related to CNVs in the same chromosomal regions. However, the extent of CNVs may not be restricted to only microduplications but may also include microtriplications or even quadruplications. 4q21 microdeletion syndrome is one of these recently described syndromes. The phenotype includes growth restriction, neonatal hypotonia, severe developmental delay, absent or delayed speech, and distinct facial features. The minimal critical deleted region, which is 1.3 Mb in size, contains the PRKG2, RASGEF1B, HNRNPD, HNRPDL, and ENOPH1 genes. Here, we report a 5.4‐year‐old girl with developmental delay, absence of speech, muscular hypertension, macrocephaly, a broad forehead, frontal bossing, relatively elongated extremities, a vascular malignant hemangioma in anamnesis, and elongated sigmoid colon. aCGH revealed a microtriplication at 4q21.21‐q21.22 that was 1.61 Mb in size. This de novo microtriplication included nine genes ( BMP3, PRKG2, RASGEF1B, HNRNPD, HNRPDL, ENOPH1, TMEM150C, LINC00575, and SCD5 ) and overlapped with the minimal critical region for 4q21 microdeletion syndrome. Some clinical features of the patient were similar to those of 4q21 microdeletion (macrocephaly, frontal bossing, developmental delay, absence of speech, and anxiety), whereas others were mirrored (elongated extremities and muscular hypertension). The first identified case of a de novo microtriplication at 4q21.21‐q21.22 emphasizes the clinical significance of CNVs at 4q21 for patients with developmental delay and absence of speech. © 2016 Wiley Periodicals, Inc.